Lake Wobegon days - Keillor, Garrison (New York, N.Y., U.S.A. : Viking, 1985)
The narrator's own story is interwoven with the early history of a small town (1418 alt., 942 pop.) in Minnesota.
Home-- New Albion-- Forebears-- Sumus Quod Sumus-- Protestant-- Summer-- School-- Fall-- Winter-- News -- Spring-- Revival.
1160
Keywords: Lake Wobegon (Minn. : Imaginary place) -- Fiction; City and town life -- Fiction; Minnesota -- Fiction; Humorous fiction